Altered neurological function in mice immunized with early endosome antigen 1 - Fritzler Marvin J (BMC Neuroscience, 2004)
Abstract Background Autoantibodies directed against the 160 kDa endosome protein early endosome antigen 1 (EEA1) are seen in patients with neurological diseases. To determine if antibodies to EEA1 have a neuropathological effect, mice from three major histocompatability haplotype backgrounds (H2q, H2b and H2d) were immunized with EEA1 (amino acids 82–1411) that was previously shown to contain the target EEA1 epitopes. The mice were then subjected to five neuro-behavioural tests: grid walking, forelimb strength, open field, reaching and rotarod. Results The immunized SWR/J mice with sustained anti-EEA1 antibodies had significantly reduced forelimb strength than the control non-immune mice of the same strain, and BALB/CJ immune mice demonstrated significantly more forelimb errors on the grid walk test than the control group. Conclusions Antibodies to recombinant EEA1 in mice may mediate neurological deficits that are consistent with clinical features of some humans that spontaneously develop anti-EEA1 autoantibodies.